Verapamil-Sensitive Transport of Quinacrine and Methylene Blue via the Plasmodium falciparum Chloroquine Resistance Transporter Reduces the Parasite's Susceptibility to these Tricyclic Drugs. (26th October 2015) - van Schalkwyk, Donelly A.; Nash, Megan N.; Shafik, Sarah H.; Summers, Robert L.; Lehane, Adele M.; Smith, Peter J.; Martin, Rowena E.
Abstract : Background.  It is becoming increasingly apparent that certain mutations in the Plasmodium falciparum chloroquine resistance transporter (PfCRT) alter the parasite's susceptibility to diverse compounds. Here we investigated the interaction of PfCRT with 3 tricyclic compounds that have been used to treat malaria (quinacrine [QC] and methylene blue [MB]) or to study P. falciparum (acridine orange [AO]). Methods.  We measured the antiplasmodial activities of QC, MB, and AO against chloroquine-resistant and chloroquine-sensitive P. falciparum and determined whether QC and AO affect the accumulation and activity of chloroquine in these parasites. We also assessed the ability of mutant (PfCRT Dd2 ) and wild-type (PfCRT D10 ) variants of the protein to transport QC, MB, and AO when expressed at the surface of Xenopus laevis oocytes. Results.  Chloroquine resistance-conferring isoforms of PfCRT reduced the susceptibility of the parasite to QC, MB, and AO. In chloroquine-resistant (but not chloroquine-sensitive) parasites, AO and QC increased the parasite's accumulation of, and susceptibility to, chloroquine. All 3 compounds were shown to bind to PfCRT Dd2, and the transport of QC and MB via this protein was saturable and inhibited by the chloroquine resistance-reverser verapamil. Conclusions.  Our findings reveal that the PfCRT Dd2 -mediated transport of tricyclic antimalarials reduces the parasite's susceptibility to these drugs.